Improving the speed of adoption of agricultural technologies and farm performance through farmer groups: evidence from the Great Lakes region of Africa - Ainembabazi, John H.; Asten, Piet J.A. van; Vanlauwe, Bernard; Ouma, Emily A.; Blomme, Guy; Birachi, Eliud Abucheli; Dontsop Nguezet, Paul M.; Mignouna, Djana B.; Manyong, Victor M. (Wiley, 2017)
The article examines the effect of membership in farmer groups (MFG) on adoption lag of agricultural technologies and farm performance in Burundi, the Democratic Republic of Congo and Rwanda. We use duration and stochastic production frontier models on farm household data. We find that the longer the duration of MFG, the shorter the adoption lag and much more so if combined with extension service delivery. Farmer groups function as an important mechanism for improving farm productivity through reduced technical inefficiency in input use. We discuss the policy implications under which farmer groups are a useful channel to reduce adoption lag, and the means through which improved farm performance can be achieved.